Membangun Jiwa Wirausaha Di Era Digital Bagi Peserta Didik Smk Dharma Loka - Evelyn Wijaya; Yusnita Octafilia; Martha Ng; David David; Stefani Chandra; Sarli Rahman; Bord Nandre Aprila; Fery Martias (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
The community service activity was held at SMK Dharma Loka Pekanbaru with the theme